ANALISIS MANAJEMEN PENDEKATAN KELAS DALAM MENINGKATKAN KEDISIPLINAN PESERTA DIDIK SDN 002 SUNGAI PINANG - Samsul Adianto; Euis Kusumarini; Nurhayati Nurhayati (Inteligensi : Jurnal Ilmu Pendidikan, 2020)
This study aims to determine whether the application of Classroom Approach Management can improve the Discipline of Class VB Students at SDN 002 Sungai Pinang in 2020. This research was conducted at SDN 002 Sungai Pinang from April to July 2020. This research design used a qualitative research design. The population of this study used students of class VB SDN 002 Sungai Pinang. The sampling technique used purposive sampling with the research subjects namely the teacher, the principal and four students. This study uses data collection techniques with interviews and documentation. The data analysis technique used was data collection, data reduction, data presentation and conclusion drawing. Checking the validity of the data using source triangulation techniques. Based on the results of research and interviews, it is known that there are ten approaches that are applied by teachers in the classroom in improving discipline. The teacher takes this approach in turn according to the classroom situation. However, of the ten applied approaches that are more widely applied and have an influence in increasing student discipline, namely the power approach, for example, the imposition of sanctions, the freedom approach, for example, including students in making rules in class, teaching approaches.